PLANNING AND DESIGN SOA ARCHITECTURE BLUEPRINT - Tulenan, Virginia (Jurnal Teknik Informatika, 2013)
Service Oriented Architecture (SOA) is a framework for integrating business processes and supporting IT infrastructure as secure, standardized components-services-that can be reused and combined to address changing business priorities. Services are the building blocks of SOA and new applications can be constructed through consuming these services and orchestrating services within a business process. In SOA, services map to the business functions that are identified during business process analysis. Upon a successful implementation of SOA, the enterprise gain benefit by reducing development time, utilizing flexible and responsive application structure, and following dynamic connectivity of application logics between business partners. This paper presents SOA reference architecture blueprint as the building blocks of SOA which is services, service components and flows that together support enterprise business processes and the business goals.Keywords: Service Oriented Architecture, SOA Reference Architecture